Adolescents Adjudicated for Sexual Offending: Differences Between Sexual Reoffenders and Sexual Non-Reoffenders - Siria, Sandra (Journal of interpersonal violence, 2022)
Although a very small group of adolescents adjudicated for sexual offending (ASO) will persist into adulthood, the use of official records of sexual recidivism after long-term follow-up periods underrates the repetition of sexually coercive behaviors during adolescence. Additionally, limited research has considered sexual reoffending as a criterion to classify this heterogeneous population. The aims of this study were to determine the prevalence of ASO who engaged in repetitive sexual offending before their adjudication, and to use it as a classification criterion to examine the differential characteristics associated with each group. A sample of 73 adjudicated ASO in Spain was examined. They were divided into sexual reoffenders (SR) (n = 34) and sexual nonreoffenders (SNR) (n = 39). An ex post facto research design was carried out. Assessments included reviews of official files, interviews with professionals in charge, and interviews with the ASO in which the Interpersonal Reactivity Index (IRI) was administered. Descriptive analyses were conducted for all variables and Odds Ratio (OR) was used to compare intergroup differences. Results showed that SR had 12.95 times the odds of sexual victimization, 6.91 times the odds of having lived in a sexualized family environment, and 3 times the odds of bullying victimization. Deviant sexual fantasies were exclusively present among SR (44%). Significant differences between groups were also found in some sexual crime variables but not on the empathy scale. These results have implications for the distinction between ASO who have repeatedly engaged in sexually coercive behavior and those who engaged in a single event of sexual offending. The identification of specific risk factors and criminogenic needs for each group would benefit court decisions and more tailored interventions.